Clinical characteristics and outcomes of pregnant women admitted to the emergency department - Sanalp Menekse, Tugba; Soykan Sert, Zekiye; Sert, Ekrem Taha (Annals of Medical Research, 2022)
Aim: To evaluate the demographic and obstetric characteristics, complaints, and outcomes of pregnant patients who presented to the emergency department (ED).Materials and Methods: Pregnant women aged 18 years and over who presented to the ED of our hospital between September 30, 2020, and September 30, 2021, were retrospectively included in the study. The clinical data of the patients were obtained from the hospital’s electronic database. The patients’ age, gestational week, complaints at the time of presentation to ED, distribution of diagnoses, and outcomes (admission and discharge) were recorded.Results: A total of 561 pregnant patients were included in the study. The mean age of the patients was 27.6±5.7 years, and 42.6% were in the third trimester. We found that 59.8% of the cases presented to ED for obstetric reasons and 40.2% for non-obstetric reasons. While 55.5% of the patients with obstetric presentations underwent emergency delivery, 51.3% of the those with non-obstetric presentations had respiratory tract infections. In addition, 90.7% of the patients with obstetric presentations were hospitalized. The hospitalization rate of those with obstetric presentations was statistically significantly higher than the non-obstetric presentation group (p
Keywords: Emergency department; Obstetric; Outcomes; Pregnancy